Error Analysis on English Consonant Pronunciation Produced By The Fifth Semester Students of English Education Department - Ice Trysnawati; Sri Mulyani; Asfiah Syam (Fakultas Sastra - Universitas Muslim Indonesia, 2020)
This research aimed to find out the mispronunciation of consonants and the most frequently mispronounced consonants produced by the fifth semester students of the English Education Department at Institut Parahikma Indonesia in the academic year 2020/2021. This research applied descriptive quantitative research method. The participants were 14 students from the fifth semester of English Education Department. The data were collected by using a reading text. The data were analyzed quantitatively through three steps: 1) identifying errors; 2) calculating errors, and 3) drawing conclusion. The result of the research showed that nine (9) consonants were mispronounced by the students and one consonant was error-free. The mispronounced consonants were / v /: (19.5%), / ð /: (18.8%), / θ /: (15.5%), / z /: (14%), / dʒ /: (9%), / ɡ /: (8%), / w /: (6.2%), / r /: (4.6%), / ŋ /: (4.3%) and / b /: (-) were error-free consonant. Meanwhile, The most frequently mispronounced consonants were / v / and / ð /.